Structural, Optical and Dielectric Properties of Lithium Fluoro and Chloroand Magnesium Chloro Phosphate Glasses - Loh, Yen Nee (2005)
A series of lithium fluoro phosphate glass, (LiF), (P205)1-xw ith x = 0.1 to x = 0.6; lithium chloro phosphate glass, (LiCl), (P205)1-wx ith x = 0.1 to x = 0.6 both in the interval of 0.05 and magnesium chloro phosphate glass, (MgC12)x (P205)1-x with x = 0.1 to x = 0.45 in the interval of 0.05 glasses were prepared by a single-step melting process with LiF, LiC1, MgC12 and P2O5 as starting materials. The amorphous structure of the samples was evident by the XRD spectrum. The short range structures of those binary phosphate samples were examined by Fouriertransform infrared (FTIR) spectroscopy. The densities of the samples were measured as supportive data for the investigations. Ellipsometer is used to determine the samples refractive indices. The results of refractive indices reveal the homogeneity of samples and it was found to be depended on the glass composition. The optical absorption spectra of these glasses were measured using a UV-Vis spectrophotometer and recorded. The Urbach rule has been applied to evaluate the fundamental absorption edges for all the glasses from the obtained spectrum. The optical band gaps were calculated from the absorption edge and it was found that the optical band gap, E, depended on the glass composition. The value of Eopt was found to be erratic although it still shows a decreasing pattern with the increasing mole fraction of network modifier. The dielectric properties of the samples were also measured using a Novocontrol Novotherm High Dielectric Resolution Analyser. The results showed that the dielectric constant and the dielectric loss factor decreased with frequency and increased with temperature.